MWCNTs coated silica microfiber sensor for detecting Mg2+ in de-ionized water - Yasin, Moh; Irawati, Ninik; Isa, Naimah Mat; Harun, Sulaiman Wadi; Ahmad, Fauzan (Elsevier, 2018)
A multi-walled carbon nanotubes (MWCNTs) coated silica microfiber sensor for the detection of magnesium ions (Mg2+) in de-ionized water is reported. The change refractive index in the MWCNTs when sensor is being immersed in the magnesium solution is used as the working principle. The silica microfiber probe is fabricated by flame brushing technique and has a waist diameter of 6 μm with tapering length of 3 cm. The performance of the sensor is suitable for the low concentration ranging from 0.1% to 0.5% and as the sensitivity (Mg2+) solution increased, the transmitted power decreased. The results demonstrate that MWCNTs coated silica microfiber has many advantages such as low cost, enhanced sensitivity of the sensor and capability of a real time monitoring detection of (Mg2+).